Individual chronotype as a predictor of treatment effectiveness - M. Yu. Gerasimchuk (Обозрение психиатрии и медицинской психологии имени В.М. Бехтерева)
A study was conducted on depressive patients (n = 100, F.31-33, mean age 48 ±16 yrs) to identify factors for improve treatment effectiveness, clinical and chronobiological characteristics were evaluated. Positive predictors included morningness, disease duration less than 1 year, low severity of depression, symptoms of anxiety while eveningness, disease duration more than 10 years, symptoms of hypochondria, high severity of depression were assessed as negative. Eveningness was associated with family history of mood disorders, early onset, severe disease, prescription of antidepressants in the morning (the proportion of responders was higher among TCAs and SSRIs groups); morningness with preponderance of women - in the evening.